Association of CD4 count with anthropometric parameters and metabolic alterations in treatment naive human immunodeficiency virus infected patients - C. N., Arunraj; S., Sundeep (International Journal of Research in Medical Sciences, 2019)
Background: Body fat abnormalities and metabolic derangements are well known to occur in human immunodeficiency virus (HIV) infection. The objective of present study was to evaluate the anthropometric parameters, fasting lipid profile and fasting blood sugar in treatment naïve HIV patients and to assess any relation with CD4 count. Methods: Anthropometric measurements, latest CD4 count were recorded from HIV patients. Blood was collected from patients for lipid profile and sugar measurements. Results: Anthropometric parameters showed a gradual increase in waist circumference (WC), increase in waist hip ratio (WHR) and decrease in body mass index (BMI) as CD4 count declined. Fasting lipid profile showed a gradual decrease in total cholesterol, low density lipoprotein cholesterol (LDL-C) and high density lipoprotein cholesterol (HDL-C) and increase in triglycerides (TG) and very low density lipoprotein cholesterol (VLDL-C) as CD4 count declined which were statistically highly significant (P<0.001). Compared to higher CD4 group (350-500/ mm3), the lower CD4 group (<50/mm3) showed a decrease in mean total cholesterol by 60 mg/dL, LDL-C by 76 mg/dL and HDL-C by 13 mg/dL. The increase in mean TG and VLDL-C were 154 mg/dL and 30 mg/dL respectively. Comparison of fating blood sugar (FBS) between CD4 groups showed a gradual rise in FBS as CD4 count declined. Conclusions: As CD4 count declines, metabolic alterations occur in treatment-naïve HIV patients with substantial decrease in serum total cholesterol, HDL-C, LDL-C and an increase in TG and VLDL-C and increased incidence of impaired FBS. Morphological alteration in advanced HIV is evidenced by increased WC, WHR and decreased BMI.